Evaluating the Women's Empowerment and Leadership Initiative: Supporting mentorship, career satisfaction, and well‐being among pediatric anesthesiologists. Issue 1 (11th November 2022) - Deutsch, Nina; Yanofsky, Samuel D.; Markowitz, Scott D.; Tackett, Sean; Berenstain, Laura K.; Schwartz, Lawrence I.; Flick, Randall; Heitmiller, Eugenie; Fiadjoe, John; Lee, Helen H.; Honkanen, Anita; Malviya, Shobha; et al.
Abstract: The Society for Pediatric Anesthesia launched the Women's Empowerment and Leadership Initiative (WELI) in 2018 to empower highly productive women pediatric anesthesiologists to achieve equity, promotion, and leadership. WELI is focused on six career development domains: promotion and leadership, networking, conceptualization and completion of projects, mentoring, career satisfaction, and sense of well‐being. We sought feedback about whether WELI supported members' career development by surveys emailed in November 2020 (baseline), May 2021 (6 months), and January 2022 (14 months). Program feedback was quantitatively evaluated by the Likert scale questions and qualitatively evaluated by extracting themes from free‐text question responses. The response rates were 60.5% (92 of 152) for the baseline, 51% (82 of 161) for the 6‐month, and 52% (96 of 185) for the 14‐month surveys. Five main themes were identified from the free‐text responses in the 6‐ and 14‐month surveys. Members reported that WELI helped them create meaningful connections through networking, obtain new career opportunities, find tools and projects that supported their career advancement and promotion, build the confidence to try new things beyond their comfort zone, and achieve better work–life integration. Frustration with the inability to connect in‐person during the coronavirus‐19 pandemic was highlighted. Advisors further stated that WELI helped them improve their mentorship skills and gave them insight into early career faculty issues. Relative to the baseline survey, protégés reported greater contributions from WELI at 6 months in helping them clarify their priorities, increase their sense of achievement, and get promoted. These benefits persisted through 14 months. Advisors reported a steady increase in forming new meaningful relationships and finding new collaborators through WELI over time. All the members reported that their self‐rated mentoring abilities improved at 6 months with sustained improvement at 14 months. Thus, programs such as WELI can assist women anesthesiologists and foster gender equity in career development, promotion, and leadership.